Cloud Computing : A Practical Approach - Velte, Anthony T.; Velte, Toby J.; Elsenpeter, Robert (New York McGraw-Hill, 2010)
Cloud Computing: A Practical Approach provides a comprehensive look at the emerging paradigm of Internet-based enterprise applications and services. This accessible book offers a broad introduction to cloud computing, reviews a wide variety of currently available solutions, and discusses the cost savings and organizational and operational benefits. You'll find details on essential topics, such as hardware, platforms, standards, migration, security, and storage. You'll also learn what other organizations are doing and where they're headed with cloud computing.
Includes index
Keywords: Công nghệ thông tin